(Un)finished transition. Stock of knowledge in Poland, 1924–2012 - Wallusch, Jacek (Economics and Business Review, 2015)
Technological underdevelopment of the Polish economy has been remarkably persistent. In this paper I focus on the stock of knowledge, approximated by the 10% depreciation rate of accumulated patents granted in Poland, to show its longterm structure and to distinguish its growth phases. I test for long memory and run a Markov-switching autoregressive model. The stock of knowledge is found to be nonstationary and mean reverting. I also discover two well-separated regimes representing slower and faster changes in the stock of knowledge. The latter regime characterises the years between the 1920s and mid-1950s (interrupted by the Great Depression and World War II), mid-1970s and the period after accessing the EU.